Vrednotenje modelov univerzitetnih knjižnic v Avstriji, Nemčiji in Sloveniji - Sapač, Irena (Knjižnica, 2005)
The article discusses the evaluation of models of university libraries in Austria, Germany and Slovenia. Evaluation in this case means the estimated value of a specific service, and in this article it is the library service. The author tries to evaluate the models of university libraries with qualitative and quantitative methods. In the research, she is interested in the position of the university library in the states' library system, the legal and financial frame, historical development, organizational structure, staff, total library holdings, the increased library holdings, users, implementations of information technology, and the vision of the implementation of organisational and tehnological novelities. She tries to ascertain how a specific library satisfies the users' needs and also tries to define the advantages and disadvantages in the library's functioning. The author states that an optimal model, which would be ideal in all European states, doesn't exist, there exists just an optimal model within a particular state or region.
Keywords: univerzitetne knjižnice; organizacijski modeli; organizacija poslovanja; Austria; Avstrija; Germany; Nemčija; Slovenia; Slovenija